(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A prevalent illness that is linked to morbidity and a poor quality of life is insomnia or sleeplessness. One of yoga’s six purification practices is called trataka. According to the literature, trataka may aid in reducing insomnia and it is closely associated with mental health. The effectiveness of trataka on the quality of mental health for those people who have it was examined in this study. Fifty insomniac subjects were chosen which divided half in control group and experimental group they underwent trataka (45 minutes) alternate days per week for 6 weeks. The Mental Health Inventory (MHI) was used to evaluate the quality of sleep before and after the intervention. This study revealed a significant increase in MHI global score and its associated sub-scale scores following the intervention. When it comes to treating insomnia, reducing its intensity, and enhancing a person’s mental health, trataka may be an option.